Ecosystem approach to assessing the effectiveness of socially oriented entrepreneurship (Journal of Economic Research & Business Administration, 2024)
The most pressing task of modern society is to ensure sustainable development based on inclusive economic growth. In this regard, the importance of social and socially oriented entrepreneurship in achieving the Sustainable Development Goals is increasing. Scientific research discusses various aspects of the phenomenon of social entrepreneurship. The least developed in the applied aspect is the issue of the effectiveness of social entrepreneurship and its assessment. The purpose of the study is to determine the conceptual foundations of the ecosystem approach to assessing the effectiveness of socially oriented entrepreneurship to improve the sustainability of the socio-economic development of regions.The methods include bibliographic analysis, modeling and statistical analysis. Bibliographic analysis revealed the need to distinguish between external and internal efficiency of social entrepreneurship. Modeling allows this to be implemented based on the ecosystem approach. Statistical analysis revealed that social entrepreneurship develops in rural areas much more slowly than in cities. Such imbalance cannot contribute to sustainable growth of regions in Kazakhstan.The results include literature analysis and identification of current research areas in the field of social entrepreneurship effectiveness assessment. The need to develop a social entrepreneurship ecosystem at the regional level is substantiated. The structure of the regional ecosystem as a complex institutional system is developed. The role of the state in the formation of this ecosystem is characterized. The types of ecosystem resources that determine internal efficiency are substantiated. The definition of the effectiveness of socially oriented entrepreneurship is formulated.  An algorithm for assessing the effectiveness of socially oriented entrepreneurship has been developed    The ecosystem approach allows classifying social entrepreneurship into non-profit and commercial, taking into account not only external but also internal parameters, such as inclusiveness, density of connections and synergy. A statistical analysis of social entrepreneurship in Kazakhstan in the regional context is carried out.The findings highlight the need to develop socially oriented entrepreneurship as a key element of an inclusive economy for sustainable socio-economic development of regions. When developing public policy aimed at achieving sustainable development goals, one should rely on the concept of social entrepreneurship and its ecosystem, as well as on assessing its effectiveness.Key words. sustainable growth, socialization, inclusion, social impact, effectiveness of social entrepreneurship, regional ecosystem model